2016
DOI: 10.1039/c5nj02545a
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of Fe3O4/carboxylate-rich carbon composite and its application for Cu(ii) removal

Abstract: A magnetically separable adsorbent, Fe3O4/carboxylate-rich carbon composite was synthesized via a facile one-step low temperature carbonization process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…Hence, in this work, CRC/Fe 3 O 4 magnetic composites were synthesized by the sol-gel self-combustion method ( Qu et al, 2016 ). The CRC/Fe 3 O 4 samples were characterized and applied in the Fenton process to degrade MB.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in this work, CRC/Fe 3 O 4 magnetic composites were synthesized by the sol-gel self-combustion method ( Qu et al, 2016 ). The CRC/Fe 3 O 4 samples were characterized and applied in the Fenton process to degrade MB.…”
Section: Introductionmentioning
confidence: 99%
“…Cấu trúc và thành phần tinh thể của Fe3O4@CRC được khảo sắt bằng phổ XRD. Từ Hình 2a cho thấy trong giản đồ XRD [21]. Phổ hồng ngoại FITR (Hình 2b) được sử dụng để xác định các nhóm chức bề mặt của vật liệu Fe3O4@CRC.…”
Section: Các đặC Trưng Của Vật Liệuunclassified
“…Study. For kinetic study, a time-dependent adsorption experiment was performed with a nanosorbent dose of 0.25 g L −1 and 20 ppm Cu 2+ solution under stirring for different intervals of time (3,5,15,30,60,120,240,360,480,960,1440, and 2400 min). Obtained adsorption results were fitted in with pseudo-first-order, second-order, and intraparticle diffusion models to describe the kinetic characteristics of the nanosorbent material.…”
Section: Adsorption Experiments For Kinetics and Isothermmentioning
confidence: 99%
“…26−29 Qu et al used Fe 3 O 4 / carboxylate-rich carbon composites for Cu 2+ removal and showed a comparison with various Fe 3 O 4 nanostructure-based adsorbents reported in the literature, which exhibit Cu 2+ adsorption capacity below 67 mg g −1 . 30 Xu et al prepared iron oxide nanoparticle-immobilized Phanerochaete chrysosporium and found their Pb 2+ removal capacity of 176.3 mg g −1 . 31 Recently, amino-functionalized magnetite/kaolin clay has been reported for enhanced removal of Pb 2+ , Cu 2+ , and Cd 2+ with adsorption capacities of 86.6, 16.5, and 22.1 mg g −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation